An economy-wide perspective on aspects of electricity supply in Myanmar - Dirk van Seventer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Myanmar's economy has experienced political and economic transformations since 2011 by means of diverse economic reforms. However, the power sector is still struggling to fulfil electricity demand. This study will examine aspects of the electricity sector in an economy-wide perspective by means of multiplier analysis based on a recent Social Accounting Matrix for Myanmar. The paper begins by providing a brief scene-setting context for the electricity sector in Myanmar and discusses its developmental issues in the last decade or so, since the start of the recent political and economic liberalization. Some of these issues will be the subject of a multiplier modelling effort. The modelling shows that insufficient and infrequent supply of electricity can have far-reaching consequences, some of which are not obvious at first. This highlights the importance of understanding the network of inter-industry interactions even in an economy of which the different elements are not as interconnected as in many other countries.
Keywords: E16; O1; O2; O53; 330; economy-wide perspective; Social Accounting Matrix; multiplier analysis; electricitysector; Myanmar